The Anchorage Performance and Mechanism of Prefabricated Concrete Shear Walls with Closed-Loop Rebar - Yufen Gao; Zheng Yang; Lu Chen; Shengzhao Cheng; Zhongshan Zhang (Buildings)
To thoroughly investigate the anchorage performance of a novel prefabricated concrete shear wall system assembled by anchoring closed-loop rebar, rebar pull-out tests were conducted. The effects of different rebar distribution forms, closed-loop rebar anchoring heights, and dowel rebar diameters on anchorage performance were considered. Strain measurements at key points were taken, and the failure modes and peak loads of shear walls with various closed-loop rebar assemblies were obtained. The results indicated that the rebars in all specimens fractured, with peak loads ranging from 90 kN to 100 kN, satisfying the anchorage requirements of the rebar. This demonstrates that even when the anchorage length of the rebar is less than specified, the method of assembling by anchoring closed-loop rebar can still provide good anchorage performance. Moreover, steel bars and concrete have different damage and failure characteristics under different load levels. This research also indicates that specimens with uniformly distributed closed-loop rebar exhibit superior anchorage performance compared to those with adjacent distribution. Furthermore, increasing the overlapping height of the closed-loop rebar contributed to enhancing the safety margin of the anchorage, while the diameter of the dowel rebar (similar to stirrups) had a relatively minor effect on the anchorage performance. These findings provide a scientific basis for the design and construction of prefabricated concrete shear walls with closed-loop rebar.